The Impact of Digital Information Flow on Generation Z’s Religious Awareness - Tohari, Achmad (Jurnal Penelitian Agama, 2024)
This study explains how the religiosity of Generation Z in carrying out religious life in the midst of the flow of digital information, they as a generation that has been surrounded by technology in everyday life with all its advantages have not been able to sort information and tend to ignore moral and ethical values, so that in their relationships they seem individualistic and ambitious, this has an impact on their religiosity in everyday life. This study uses descriptive analysis methods and literature study methods in data collection. This study concludes that the religiosity of Generation Z as a young generation in the era of technological development has not achieved a good understanding of religious awareness, which seems individualistic and difficult to socialize, they consider religious issues more as mere formalities, in an effort to increase awareness of Gen-Z understanding, various efforts need to be made. First, instilling the values ​​of religious moderation in education provided by educators. Second, increasing the involvement of the younger generation in various innovative national programs. Third, balancing mainstream movements on campus and schools to strengthen and understand religious moderation.